2019
DOI: 10.1111/bjh.16355
|View full text |Cite
|
Sign up to set email alerts
|

The role of allogeneic stem cell transplantation in the management of acute myeloid leukaemia: a triumph of hope and experience

Abstract: Acute myeloid leukaemia (AML) is the commonest indication for allogeneic stem cell transplantation (allo-SCT) worldwide. The accumulated experience of allografting in AML over the last four decades has provided critical insights into both the contribution of the conditioning regimen and the graft-versus-leukaemia effect to the curative potential of the most common form of immunotherapy utilised in standard clinical practice. Coupled with advances in donor availability and transplant technologies, this has resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 137 publications
(158 reference statements)
0
73
0
1
Order By: Relevance
“…These risks include high treatment toxicity, infectious complications, graft-versus-host-disease (GVHD), transplant failure, and relapse. 77 Evaluating suitable patients for transplantation and patients at risk for complications is therefore crucial before starting conditioning therapy. Shouval et al 78 identified key variables to predict overall survival 100 days after transplantation in an analysis of .25 000 leukemia patients from the European Society for Blood and Marrow Transplantation with various ML techniques; they validated the scoring system in a prospective cohort study of 1848 patients from the Italian national transplant network.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…These risks include high treatment toxicity, infectious complications, graft-versus-host-disease (GVHD), transplant failure, and relapse. 77 Evaluating suitable patients for transplantation and patients at risk for complications is therefore crucial before starting conditioning therapy. Shouval et al 78 identified key variables to predict overall survival 100 days after transplantation in an analysis of .25 000 leukemia patients from the European Society for Blood and Marrow Transplantation with various ML techniques; they validated the scoring system in a prospective cohort study of 1848 patients from the Italian national transplant network.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Dans le traitement des leucémies aiguës myéloblastique, elle est indiquée chez les patients en première rémission, pour les leucémies à bas risque et avec une maladie résiduelle indétectable [52] . L’allogreffe reste le traitement de référence pour les leucémies aiguës myéloblastiques de l’adulte en première rémission chez ceux qui ont un risque de récidive de 35 à 40 %, en cas d’anomalies cytogénétiques péjoratives ou de myélodysplasie préexistante [53] , [54] . Elle est aussi indiquée dans les leucémies aiguës lymphoblastiques de l’adulte avec anomalies cytogénétiques défavorables, en cas de phénotype pré-B et chez les patients avec un taux de leucocytes élevés au diagnostic.…”
Section: Cellules Souches Hématopoïétiques Et Cellules Car-tunclassified
“…In addition, in some patients the GvL effect is not sufficient to eradicate patients' leukemia. Therefore, more effective strategies are needed to treat patients with recurrent disease after alloHSCT [2].…”
Section: Introductionmentioning
confidence: 99%